Transcriptome Profiling of Anhidrotic Eccrine Sweat Glands Reveals that Olfactory Receptors on Eccrine Sweat Glands Regulate Perspiration in a Ligand-Dependent Manner - Naoya Murayama; Takafumi Miyaki; Daisuke Okuzaki; Yasuaki Shibata; Takehiko Koji; Asuka Inoue; Junken Aoki; Hideki Hayashi; Yoshimasa Tanaka; Hiroyuki Murota (Elsevier, 2023)
Sweat maintains systemic homeostasis in humans. Although sweating disorders may cause multifaceted health problems, therapeutic options for sweat disorders have not yet been established. To gain new insight into the mechanism underlying the regulation of perspiration, we compared eccrine sweat gland transcriptomes from hidrotic and anhidrotic lesions from patients with anhidrosis and found out that olfactory receptors were expressed differentially in anhidrotic and hidrotic eccrine sweat glands. We then confirmed OR51A7 and OR51E2 expression in human eccrine sweat glands by in situ hybridization and immunohistochemistry. An alkaline phosphatase−TGFα shedding assay revealed that β-ionone activates G-proteins through OR51A7 or OR51E2. The effect of topically applied β-ionone on sweating was examined with the quantitative sudomotor axon reflex test, which showed that responses to β-ionone differed between sexes. Topical β-ionone attenuated female sweating and augmented male sweating. Taken together, this study suggests that olfactory receptors expressed in eccrine sweat glands may regulate sweating in response to odorous ligands on the basis of sex. These unexpected results indicate that olfactory receptors may modulate sweating and that olfactory receptor modulators may contribute to the management of sweat disorders.